MOBILITAS SIRKULER DI DESA SEA SATU KECAMATAN PINELENG KABUPATEN MINAHASA - Simon Samuel A. Wales; Agnes E. Loho; Jean F. J. Timban (Sam Ratulangi University, 2018)
This study aims to determine the circular mobility that occurs in the Sea Satu Village, Pineleng Sub-district of Minahasa Regency, based on several aspects. The data needed to answer for the objectives is primary data and secondary data. Data were collected from direct interviews with respondents, as well as other data taken directly at the Village Head Office. The data were analyzed descriptively and described based on aspects related to circular mobility in this Sea Satu Village. The characteristics of circular mobility practitioners in Desa Sea Satu Village are due to aspects of age, gender, number of family members, education level, occupation type (TNI/POLRI), civil servant, private employee, entrepreneur, Honorer, Craftman, Driver and Ojek) , the number of dependents. The incentive factors are the types of transportation, mileage, and the towing factors are the status of home ownership, and the cost of living.*jnkd*.